RESEARCH ON THE EFFECT OF NON-TRANSITIONAL RAW MATERIALS ON THE RHEOLOGICAL INDICATORS OF THE SEMI-FINISHED PRODUCTS OF FORMED POTATO CHIPS - Alina KOVTUN (Stefan cel Mare University of Suceava, 2019)
The paper considers the current state and prospects of enrichment of formed potato chips with bran, pulp and cryopowder containing from 14 to 40% of food fibres. The importance of the use of food fibres, which is connected with the prevention of alimentary-dependent diseases, has been substantiated. The optimum size of the degree of grinding of rye bran, barley bran, pumpkin seeds pulp, broccoli cryopowder and red beetroot cryopowder and their influence on rheological parameters of semi-finished products have been determined. The influence of temperature and time on the change of maximum viscosity of model solutions of potato semi-finished potato products has been investigated.